Gaya Kepemimpinan Demokratik, Karakteristik Individu, Remunerasi, Dan Pengaruhnya Terhadap Kinerja Anggota Polisi Republik Indonesia (Studi Pada Anggota Polisi Resort Kota Manado) - hamsi, Hamsi- (Universitas Sam Ratulangi, 2015)
The purpose of this research is to identify the Democratic Leadership Style, Individual Characteristics, Remuneration, and its effects on the Job Performance of the Police Force. The sampling technique used was simple random sampling. The population of this research is the Police Officers in Kepolisian Resort Kota Manado as many as 537 people. Sample size determined was 310 officers according to the Isaac-Michael table on the significance level of 5%, however maybe analyzed further as many as 219 officers. The research method used was the multiple linear regression analysis. The tool was used to find out the influence of independent variables to dependent variables. The research findings show that Democratic Leadership Style and Remuneration have significant effect on the performance of the Police Officers, while Individual Characteristics does not have any significant effect on the performance of the Police Officers. Keywords:Â Democratic Leadership Style, Individual Characteristics, Remuneration, Police Force